Benefits of Snoezlen (TM) and People with severe and profound developmental disabilities - Kirschbaum, Lindsey (My University, 2009)
Multisensory Environments (MSEs) are growing in popularity as an environment known for relaxation and independence. However, the purpose of these environments, or room, may be lost by misuse of the facilitation of the room. The aim of this manuscript is to explain what the therapeutic outcomes are, what trainings or certifications are needed to facilitate a successful MSE session, and participants reactions to MSE's in terms of lowering or increasing arousal. The remodel of an existing MSE for persons with severe developmental disabilities is explained.
Keywords: Sensory stimulation; Developmentally disabled -- Rehabilitation